2002
DOI: 10.1111/1467-9566.00004
|View full text |Cite
|
Sign up to set email alerts
|

‘There are no rights and wrongs in these situations’: identifying interactional difficulties in genetic counselling

Abstract: The rapid scientific and technological advances in the field of human genetics have created an ever-widening gap in knowledge and understanding between those specialists who are involved with them and the general public who are the intended beneficiaries. Genetic counselling is seen as an important way of addressing this gap. Whilst there is a growing literature on genetic counselling, this has tended to focus on quantitative measures of outcome. However, there is a growing recognition that genetic counselling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…Importantly, this technique may contradict client-led counselling. 45 Rather it may be better to acknowledge that silence or limited communication may be a protective response to medical diagnoses 46 and, despite counsellors' efforts, children may find it hard to distinguish between genetic counselling and other medical consultations. Indeed, it has been proposed that 'Denial is perhaps the most straightforward [strategy to cope with genetic threat] -to try to ignore the issue, refuse to discuss it and to keep well away from geneticists' (Richards,47 pp.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this technique may contradict client-led counselling. 45 Rather it may be better to acknowledge that silence or limited communication may be a protective response to medical diagnoses 46 and, despite counsellors' efforts, children may find it hard to distinguish between genetic counselling and other medical consultations. Indeed, it has been proposed that 'Denial is perhaps the most straightforward [strategy to cope with genetic threat] -to try to ignore the issue, refuse to discuss it and to keep well away from geneticists' (Richards,47 pp.…”
Section: Discussionmentioning
confidence: 99%
“…If genetic counselling is a communication process, it can only be fully understood when studied as such. 23 Nevertheless, even when results of our study showed that experts highlighted the consultant-centred practice as a high standard of quality during PST counselling, tools that are currently being used did not specifically address the process of genetic counselling.…”
Section: Discussionmentioning
confidence: 63%
“…21,22 Previous studies on quality of genetic counselling have been mainly focused on outcomes and have been frequently related to changes in reproductive behaviour and/or client knowledge among other factors, although we believe that effectiveness in genetic counselling remains fundamentally related to its process. A review by Pilnick et al 23 highlighted the gap in our knowledge of the relationship between outcome and process, emphasising the need to identify specific components of the process that results in the consultant's satisfaction and the factors that are likely to influence it. 23 In addition, we consider that quality assessment can only be achieved effectively through the use of appropriate methodological tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interpretive analysis is needed in order to better understand the ways in which social and ethical considerations involved in community genetics acquire situated meanings within institutional and political contexts. It is also required for realizing the different meanings of genetic testing for the participants, and the different arenas (public and private) in which these meanings are negotiated within the community or the network of individuals and families that are affected by genetic risk (see for example Atkin et al 2008;Pilnick 2002;McAllister 2001;Featherstone et al 2006;Raz 2005).…”
Section: Methodology and Implementationmentioning
confidence: 99%